Image Steganography Using Edge Detection Technique - Chopra, Kirti; Virk, Er. Ishpreet Singh (International Journal of Computer Sciences and Engineering, 2018)
Nowadays, the mechanisms are growing among the high speed and novel developments are accomplished day by day. Every day as a huge amount of data shared within the diverse users on the internet so the sharing of data is enhanced. In order to hide the occurrence of the communication, the steganography is utilized. In a suitable carrier such as image, video or audio this mechanism deals among the insertion of the secret message. Due to its broad utilization on the internet, the digital images are majorly preferred over the other carriers. For the implementation, the MATLAB software is utilized. In this paper, a couple of methods are utilized to embed the secret message. Those methods are original binary form and complemented form of a binary converted message, to advance security. For the embedding purpose, fuzzy edge detection technique is utilized and in order to hide the information into an image, the LSB mechanism is proposed. In the proposed work fuzzy technique will be utilized to offer more sharp edges having more data and to acquire the continuity. Huffman coding compression technique is utilized to compress the data and also to send more data on less space. The MSE, BER, and PSNR are utilized as a calculation of performance analysis.